Differentiation and positioning : Uber versus Lyft - Robson, Karen, (SAGE Business cases., 2022)
Uber and Lyft are the major players in the ride-sharing industry in the United States. Both companies have achieved a considerable amount of success in their short histories, although Uber faced a string of criticisms throughout 2017. Despite many similarities in their businesses, including offerings and pricing, the two companies have achieved distinct positions in the marketplace and have a different set of strengths and weaknesses. Through this case students can study how ride-sharing companies create value for customers, and how Uber and Lyft position their platforms differently in the marketplace.